An annotated systematical checklist of the Romanian ichthyofauna - Iftime, Alexandru; Oţel, Vasile (Zootaxa, 2025)
The ichthyofauna of Romania has long constituted the object of scientific studies; however, rapid changes in both taxonomy and the composition of local fauna require constant updating of the country species list. We attempt here to give a complete checklist of Romanian ichthyofauna, including recently extinct and introduced species, and discussing doubtful records. A discussion of the taxonomical status of recorded species is also included. We discuss 272 species (plus 2 introduced hybrids) recorded for Romania, belonging to 79 families and 31 orders. The distribution and status of treated species are also briefly delineated.